Redressing Social Inequality through Transitional Justice - Venter, Ben-Joop (Department of Political Studies, 2019)
By questioning whether addressing social inequality can be considered a form of transitional justice, this dissertation leads a critical discussion on the assumptions of traditional or narrow understandings of transitional justice, how these obscure the potential for transitional justice to tackle issues of economic and social rights violations, social inequality and other forms of structural violence, and the need for a broad understanding of transitional justice and its key components. This dissertation addresses the historical and political roots of the field and how these influenced a traditional understanding of transitional justice. Thereafter, it traces broadening understandings of the concept, evident in the changing meanings of 'justice’ and 'transition’ and its stated aims. It then considers calls for transitional justice to go beyond its focus on civil and political rights violations and to further address economic and social rights violations and structural violence, and how these challenge the traditional understanding of the concept. Drawing on the distinction between a concept and a conception, and considering transitional justice as an effectively contestable concept, this dissertation proposes a broad understanding of the concept as the pursuit of justice during a period of social or political transition in order to address past injustices and to work towards certain aspirations for the future, comprising of the key components of justice, transition, and backwards- and forwards-looking considerations. With a primary focus on criminal and restorative justice, civil and political rights, and trials and truth commissions, the traditional conception of transitional justice is ill-equipped both conceptually and practically to address issues of structural violence. Instead, a conception of transitional justice motivated by social or distributive justice is best suited to address social inequality and other forms of structural violence. Finally, this dissertation considers revolutionary Nicaragua’s attempts to redress social inequality in the areas of health, education and housing as an example of transitional justice. It is concluded that revolutionary Nicaragua’s concerted effort to address social inequality should be considered as a conception of transitional justice inspired by social and distributive justice. With growing calls for transitional justice to go beyond its traditional focus on criminal and restorative justice, scholars and practitioners stand to learn from previously overlooked examples of societies in transition tackling issues of social inequality and other forms of structural violence as a matter of transitional justice.